A comparison of fatty acid profiles in highly-demanded traditional and fA Comparison of Fatty Acid Profiles in Highly Demanded Traditional and Fast Foods in Isfahan, Irands in Isfahan, Iran - Roya Alsadat Madani; Shabnam Kermani; Masoud Sami; Zahra Esfandiari; Ebrahim karamian (Journal of Nutrition and Food Security, 2022)
Background: High consumption of fatty acids is known as a dietary risk factor for cardiovascular diseases. The aim of study was to survey of fatty acid profiles in the traditional/fast foods commonly consumed in Iran. Methods: Gas chromatography was used in the present study to determine the composition of fatty acids in 40 most popular traditional/fast foods consumed in Isfahan, Iran. The food samples were collected from 19 restaurants. Results: In all the tested samples, palmitic acid was at the highest level of saturated fatty acids (SFAs) (P < 0.05). Although in both groups of foods, the levels of trans fatty acids (TFAs) were above 2% in 30% of examined foods, the higher amounts of TFAs were found in traditional foods (P < 0.05). The results show that traditional foods contain higher levels of SFAs and TFAs than fast foods. Conclusions: The alarming findings of the present study should compel the relevant authorities in Iran to adopt and implement appropriate policies that systematically and continually control the types of food prepared and served in restaurants in order to minimize the intake of SFAs and TFAs.